Monitoring innovation in education to improve education policies and outcomes in OECD countries - Stéphan Vincent-Lancrin (IUL Research, 2020)
Developing the ability to measure innovation as well as its drivers and effects is a first step to refining innovation policies and understanding how innovation can be used to improve education. Developing metrics also aims to set the basis for cumulative work on educational innovation and innovation policy in education by providing countries with indicators that can be regularly updated over time. The paper shows how this could draw on existing efforts in other sectors than education, then presents a recent measurement attempt at the international level using existing international education databases (TIMSS, PIRLS and PISA). After defining innovation and presenting the methodology, the paper shows where process innovation lay in education in Italy and in OECD countries. The conclusion highlights the link between innovation and improvement and notes some of the limitations of the current approaches.